2021
DOI: 10.5194/bg-18-1185-2021
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification in soil as a function of oxygen availability at the microscale

Abstract: Abstract. The prediction of nitrous oxide (N2O) and of dinitrogen (N2) emissions formed by biotic denitrification in soil is notoriously difficult due to challenges in capturing co-occurring processes at microscopic scales. N2O production and reduction depend on the spatial extent of anoxic conditions in soil, which in turn are a function of oxygen (O2) supply through diffusion and O2 demand by respiration in the presence of an alternative electron acceptor (e.g. nitrate). This study aimed to explore controlli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 84 publications
0
50
0
Order By: Relevance
“…For IMVs, we found oxygen demand indicator (e.g., O2 concentration or flux, CO2 flux, CH4 flux), N mass balance related variables (e.g., N2 flux, soil NO3 -, soil NH4 + , N leaching) and soil water and temperature, can be used to better constrain the processes and therefore improve the KGML performance. Rohe et al (2021) also indicated the importance of O2, CO2 and N2 soil fluxes for N2O predictions. In addition, the layerwise soil observations (e.g., soil NO3 -, soil VWC) at 0-30 cm depth can be used to significantly improve the KGML model quality, according to our feature importance analysis (Fig.…”
Section: Limitation and Possible Improvementmentioning
confidence: 84%
“…For IMVs, we found oxygen demand indicator (e.g., O2 concentration or flux, CO2 flux, CH4 flux), N mass balance related variables (e.g., N2 flux, soil NO3 -, soil NH4 + , N leaching) and soil water and temperature, can be used to better constrain the processes and therefore improve the KGML performance. Rohe et al (2021) also indicated the importance of O2, CO2 and N2 soil fluxes for N2O predictions. In addition, the layerwise soil observations (e.g., soil NO3 -, soil VWC) at 0-30 cm depth can be used to significantly improve the KGML model quality, according to our feature importance analysis (Fig.…”
Section: Limitation and Possible Improvementmentioning
confidence: 84%
“…4.2.4). The slow increase in the denitrifier biomass that Coup modeled in the silt-loam soil could be the reason that the modeled ansvf is orders of magnitude smaller than the ansvf measured in another silt-loam soil of similar WFPS (Rohe et al, 2021). This non-realistic, too small and slowly increased denitrifier community led therefore to low N 2 O and N 2 fluxes.…”
Section: Anaerobic Soil Volume Fraction (Ansvf)mentioning
confidence: 85%
“…Nevertheless, our study takes place in the air capacity range while thinner pores remained water saturated (Figure S1). Thus, we can neglect O 2 diffusion as it is 10 5 times reduced in the water phase (Rohe et al, 2021). Our technical equipment in conjunction with the large bulk soil volume of 250 cm 3 enabled us to quantify the ε CT within pores up to 15 μm.…”
Section: Beneficial Use and Restrictions To Study Soil Aeration By μCtmentioning
confidence: 99%
“…Pot et al (2015) have directly measured pore-scale water configuration at high resolution and demonstrated model predictions of local water-gas phase interfaces using a lattice-Boltzmann approach (Pot et al, 2015). The threedimensional distribution by water and air-filled pores has profound impact on soil reducing conditions, because O 2 diffusion coefficients were drastically curtailed by five orders of magnitude due to water filled-pores (Rohe et al, 2021). Thus, the electrode responds to changes in ε in close vicinity of the Pt surface because it further influences the electron availability due to the presence or absence of O 2 .…”
Section: Introductionmentioning
confidence: 99%